The effect of dorsal cochlear nucleus ablation on tinnitus in rats - Brozoski, Thomas J.; Bauer, Carol A. (Hearing research, 2005)
A growing body of evidence implies that the dorsal cochlear nucleus (DCN) plays an important role in tinnitus. To test the hypothesis that the rostral output of the DCN is necessary for the experience of chronic tinnitus, the dorsal DCN and the dorsal acoustic stria of rats with psychophysical evidence of tinnitus was ablated. If the DCN plays a necessary role in the generation of chronic tinnitus, ablating the DCN should decrease the evidence of tinnitus in subjects previously shown to have tinnitus. Contrary to prediction, bilateral dorsal DCN ablation did not significantly ( n = 11, p = 0.707) affect the psychophysical evidence of tinnitus, and ipsilateral dorsal DCN ablation appeared to increase the evidence of tinnitus ( n = 9, p = 0.018) compared to pre-ablation performance. It was concluded that the DCN does not act as a simple feed-forward source of chronic tinnitus. Alternative hypotheses were considered, among them that elevated DCN activity following acoustic trauma triggers persistent pathological changes distributed across more than one level of the auditory system. In addition to serving as a trigger, the DCN may also modify the experience of tinnitus, since the evidence of tinnitus was enhanced by ipsilateral DCN ablation.